2016
DOI: 10.1158/0008-5472.can-15-3271
|View full text |Cite
|
Sign up to set email alerts
|

VEGFR2-Targeted Three-Dimensional Ultrasound Imaging Can Predict Responses to Antiangiogenic Therapy in Preclinical Models of Colon Cancer

Abstract: Three-dimensional (3D) imaging capabilities to assess responses to anticancer therapies are needed to minimize sampling errors common to two-dimensional approaches as a result of spatial heterogeneity in tumors. Recently, the feasibility and reproducibility of 3D ultrasound molecular imaging (USMI) using contrast agents which target molecular markers has greatly improved, due to the development of clinical 3D matrix array transducers. Here we report preclinical proof of concept studies showing that 3DUSMI of V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 51 publications
2
27
0
Order By: Relevance
“…A recent study has shown that both 3D ultrasound molecular imaging with clinical grade VEGFR2-targeted microbubbles and 3D DCE-US with FDA-approved non-targeted microbubbles could provide complementary molecular and functional in vivo information on antiangiogenic treatment effects [11]. Also, early changes in molecular ultrasound imaging signal was highly predictive of later treatment outcomes in another study in a mouse colon cancer xenograft model [33]. Our findings are complementary to these results and demonstrate for the first time that early decrease of PE and AUC values obtained by 3D DCE-US can be predictive of treatment response following several treatment administration cycles.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that both 3D ultrasound molecular imaging with clinical grade VEGFR2-targeted microbubbles and 3D DCE-US with FDA-approved non-targeted microbubbles could provide complementary molecular and functional in vivo information on antiangiogenic treatment effects [11]. Also, early changes in molecular ultrasound imaging signal was highly predictive of later treatment outcomes in another study in a mouse colon cancer xenograft model [33]. Our findings are complementary to these results and demonstrate for the first time that early decrease of PE and AUC values obtained by 3D DCE-US can be predictive of treatment response following several treatment administration cycles.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several studies have demonstrated the ability of USMI to monitor disease response to anti-angiogenic therapy 48 - 53 . Furthermore, a few studies have demonstrated that USMI can predict response to therapy in different tumor models; Streeter et al found that USMI is capable of differentiating between patient-derived xenografts that respond to aurora-A kinase inhibition and non-responders earlier than tumor volume as an indicator 54 , and Sirsi et al and Wang et al demonstrated that USMI targeting VEGFR-2 can predict tumor response to anti-angiogenic therapy before there are measurable changes in tumor volume 55 , 56 . However, to our knowledge, all previous work has used group statistics to show the effectiveness of USMI to track disease progression, and while measuring differences in response to therapy between populations can provide valuable information for the overall treatment of disease, tracking and predicting response in individuals is more relevant for clinical translation.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports have shown promise for 3D CEU imaging of tumor vasculature [3437]. Our results demonstrated a highly sensitive and versatile approach to study tumor vasculature that allows the use of several in vivo 2D and 3D imaging methods.…”
Section: Discussionmentioning
confidence: 70%